The Iraqs- Iran- relation between 1950-1980 - عيزوقي رامي; ابراهيم علاء الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
International relations are the factors that greatly influence the course of events that form a mixture of history, history and developments that occur over time, leaving their repercussions on the relations of states with each other. The events of the 20th century AD, due to the great importance of the Middle East at all levels, and its ideology at the same time, which may negatively affect the reality of the Arab Gulf region, which makes the region the foci of images, plants, plants, plants, plants, plants and plants Both Iraq and Iran enjoyed great oil wealth that formed one of the goals and ambitions of the major countries, which prompted many of them to intervene and try to ignite the fuse of war between the two parties, and play on Arab-Persian tensions as well. Persian, had an impact on changing the course of events in the region and had a negative impact on the course of ideology as the main driver of the content of the conflict, especially that the two countries had witnessed many developments on the political side after the calls of the great powers for democracy and freedom, which aimed to move from monarchies to the Republic of Fugue Those countries, for example, were held by Iraq after the British withdrawal from the Gulf in an attempt to attempt to get rid of British dependence, he nationalized his oil facilities, which posed a threat to the pro-Western regime of the Shah, which prompted Iran to hasten the declaration of conflict with Iraq for fear of losing its control over the Shatt al-Arab region, which was one of the various problems.